Diastereoselective Access to anti-β-Hydroxy Sulfoxides from Chiral Epoxides and Prochiral Sulfenate Anions: Mechanistic Insights, Scope, and Limitation - Zhang, Jian; Betkekar, Vipul V.; Suzuki, Keisuke; Ohmori, Ken (Synlett, 2023)
Reported herein is a stereoselective route to anti-β-hydroxy sulfoxides through the reaction of epoxides with sulfenate anions. Extensive experimental/computational studies revealed the dual special roles of MgBr2·OEt2, serving to generate the bromohydrin alkoxide intermediate, which undergoes nucleophilic attack on the prochiral sulfenate in a diastereoselective manner. The present study has opened a general stereoselective synthetic route to anti-β-hydroxy sulfoxides.
Keywords: epoxides; diastereoselectivity; nucleophilic substitution; sulfenate anions; hydroxy sulfoxides